Implizite Derivation und Verbstammkonversion im Dänischen - Rajnik, Eugeniusz (Wydawnictwo Naukowe UAM, 2009)
Der Beitrag setzt sich zum Ziel, die Rolle der impliziten Derivation und der Verbstammkonversion im Dänischen zu analysieren und Kriterien für ihre Klassifikation zu erarbeiten. Im Mittelpunkt der Untersuchung steht die Konstituentenstruktur der komplexen Ableitungen ohne erkennbare Suffixe. Es wird versucht, eine Typisierung von den oben genannten Bildungen sowohl unter morphologischem als auch teilweise semantischem Aspekt vorzunehmen.

The article reviews various definitions of implicit derivation and conversion as applied to Danish verbs turned into nouns. The nouns are divided into classes on the basis of their derivational history and their role in the system of the language. The conversion of verb stems, a productive word-formational type in contemporary Danish, is singled out for special treatment.
Implicit derivation and conversion of verb stems in Danish
Keywords: Implizite Derivation; Verbstammkonversion; Implicit derivation; Conversion